Surface treatment with Fenton for separation of acrylonitrile-butadiene-styrene and polyvinylchloride waste plastics by flotation - Wang, Jian-Chao (Waste management (New York, N.Y.), 2017)
Copyright © 2017 Elsevier Ltd. All rights reserved.